2021
DOI: 10.1002/aesr.202100008
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Based Separation Membranes: State of the Art and Future Trends

Abstract: As an important part of organisms, proteins are of various types, and their functions and properties are different according to their structures. Therefore, it is of great significance to develop new uses of various proteins and their derivatives, increase the reuse value of protein‐based biomass materials, and build a resource‐saving and environment‐friendly society. Protein‐based separation membranes can be used as environmentally friendly alternatives to conventional petroleum‐based separation membrane mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The accurate protein structure contributes to the great performance in water permeation. According to previous studies, AQPs can transport up to 3 billion water molecules every second, which is 5-1000 times better than conventional membranes [75,76].…”
Section: Membranes With Channel Structuresmentioning
confidence: 99%
“…The accurate protein structure contributes to the great performance in water permeation. According to previous studies, AQPs can transport up to 3 billion water molecules every second, which is 5-1000 times better than conventional membranes [75,76].…”
Section: Membranes With Channel Structuresmentioning
confidence: 99%
“…Even with the implementation of β‐barrel protein channels and peptides, AQPs remain the main biological means in water purification‐based biomimetic polymer membranes. AQP's advantage is their capability to transport up to one billion water molecules per second, with a high salt rejection efficiency [147] . Studies that optimized aquaporin‐bearing membranes demonstrated water permeability that is comparable to that of commercially available porous desalination membranes (semipermeable thin‐film composite (TFC) membranes, reverse osmosis (RO)) membranes [148–150] .…”
Section: Applicationsmentioning
confidence: 99%
“…AQP's advantage is their capability to transport up to one billion water molecules per second, with a high salt rejection efficiency. [147] Studies that optimized aquaporin-bearing membranes demonstrated water permeability that is comparable to that of commercially available porous desalination membranes (semipermeable thin-film composite (TFC) membranes, reverse osmosis (RO)) membranes. [148 -150] In planar polymer membranes, fusion of aquaporincontaining (amphiphilic block copolymer-based) vesicles on a porous substrate is a common method for the fabrication of membranes for water purification.…”
Section: Membranes For Industrial and Technological Applicationsmentioning
confidence: 99%
“…Metal oxide such as Al 2 O 3 also increases thermal and mechanical stability [254]. Another approach highlights bionanocomposite membranes with surface-immobilized selective proteins [255,256]. GO-based membranes are covalently combined with bovine serum albumin (BSA) for metal ions detection [255].…”
Section: Functionalized Polymers-based Adsorptive Membranesmentioning
confidence: 99%